Portuguese local E-government - Dias, Sílvia (2003)
The Internet, the World Wide Web and electronic commerce are transforming the way of doing business. These changes are impacting every industry in our country, including local government. The Internet offers a wide variety of opportunities to improve services to citizens and to divulge information's about the communities. In Portugal, the adherence to the Internet by local government is increasing visibly, but much more has to be done. In 1999 a first study was done in order to evaluate the situation of e-government in our country, and two years passed a new study was undertaken, this time in order to evaluate the evolution registered in this area. In this paper we describe some conclusions achieved in these studies comparing their evolution in these two years.